THE INFLUENCE OF ANTI-CORRUPTION VALUES IN HONESTY, AWARENESS, AND INDEPENDENCE ON THE APPLICATION OF THE PRINCIPLES OF ISLAMIC FINANCIAL SYSTEM - afkar, taudlikhul; Miradji, Moch. Afrizal; Hariawan, Ferry (Universitas PGRI Adi Buana, 2018)
This study aims to explain the influence of anti-corruption values ​​in honesty, awareness, and independence on the implementation of principles of Islamic financial system. Sampling technique using proportional random sampling obtained by 45 respondents from all employees of Sharia Commercial Bank in East Java. The data analysis technique using multiple linear regression because there are four variables in this research. The results showed that the value of anti-corruption values ​​in the value of honesty, caring values, and the value of independence partially or simultaneously able to give a positive influence on the application of principles of Islamic financial system. However it should be noted on the value of independence because the results showed not in line with the implementation of Islamic financial system principles